Developing an interesting electrochemical biosensing system from an enzyme inhibition study: Binding, inhibition and determination of catalase by ascorbate - Jalalvand, Ali R. (2020)
By this article, we are going to report results of one of works which has been performed on investigation of the binding and inhibition of catalase (CAT) by ascorbate (ASC). To achieve this goal, different electrochemical experiments have been performed and their data have been analyzed by conventional and chemometric methods. Conventional methods were including direct analysis of the electrochemical data by observation of them and using simple mathematical equations while chemometric analyses of the electrochemical data helped us to obtain more information which completed the previous information and gave us a new insight to the binding of the ASC with CAT. The next step of our study was devoted to the investigation of the binding of ASC with CAT by molecular docking methods which gave us new information about binding and inhibition of the CAT by ASC. All the steps gave specific information which not only confirmed each other but also gave new information which helped us to better understanding the mechanism of the binding and inhibition of the CAT by ASC. Finally, based on inhibition of the CAT by ASC, we have developed a novel impedimetric method for determination of the CAT.